2021
DOI: 10.1002/jcp.30537
|View full text |Cite
|
Sign up to set email alerts
|

IRE1 signaling regulates chondrocyte apoptosis and death fate in the osteoarthritis

Abstract: IRE1 is an important central regulator of unfolded protein response (UPR) in the endoplasmic reticulum (ER) because of its ability to regulate cell fate as a function of stress sensing. When misfolded proteins accumulated in chondrocytes ER, IRE1 disintegrates with BIP/GRP78 and undergoes dimer/oligomerization and transautophosphorylation. These two processes are mediated through an enzyme activity of IRE1 to activate endoribonuclease and generates XBP1 by unconventional splicing of XBP1 messenger RNA. Thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…Worth mention, IRE1α plays key role in chondrocytes proliferation, ECM production etc. 32 , which indicates the regulatory function of IRE1α mediated ER stress in chondrocytes proliferation and degeneration. Jacqueline et al 33 found two top risk factors for OA, age and obesity, were highly associated with ER stress, and resveratrol could mitigate early joint degeneration by inhibiting ER stress.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Worth mention, IRE1α plays key role in chondrocytes proliferation, ECM production etc. 32 , which indicates the regulatory function of IRE1α mediated ER stress in chondrocytes proliferation and degeneration. Jacqueline et al 33 found two top risk factors for OA, age and obesity, were highly associated with ER stress, and resveratrol could mitigate early joint degeneration by inhibiting ER stress.…”
Section: Discussionmentioning
confidence: 96%
“…Worth mention, IRE1α plays key role in chondrocytes proliferation, ECM production etc. 32 , which indicates the regulatory function of IRE1α mediated ER stress in chondrocytes proliferation and degeneration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When misfolded proteins accumulated in chondrocytes endoplasmic reticulum (ER), endoribonuclease was activated to generates XBP1 by unconventional splicing of XBP1 messenger RNA. Thereby promoting the transcription of UPR target genes and apoptosis [45] . Furthermore, XBP1 was essential for pro-in ammatory cytokine responses in macrophages and is dependent upon nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Under the action of RIDD, the degradation of anti-caspase-2 microRNAs triggers the activation of the apoptotic promoter caspase-2, which subsequently triggers an endogenous mitochondria-dependent apoptotic pathway [ 101 ]. Similarly, IRE1α can also activate the ASK1-JNK signaling pathway by recruiting TRAF2, triggering apoptosis through the mitochondrial pathway, which has been demonstrated in chondrocyte apoptosis [ 102 ]. When ER stress occurs, calcium homeostasis is disrupted, and a large number of calcium ions in the ER are released into the cytoplasm through RyR and IP3R protein channels.…”
Section: Link Between Caspase Family and Apoptosis In Ivddmentioning
confidence: 99%